O papel da memória no julgamento e tomada de decisão - Liberali, Jordana Folle de Menezes (2012)
This dissertation investigates the role of memory on judgment and decision-making. In order to do that we present three papers, one theoretical and two empirical as we describe next. The theoretical paper is a systematic review of 273 papers about consumer behavior, focused on the memory influence on shopping judgment and decision making. We begin presenting a general view of memory in studies about judgment and decision making. Next we present several memory concepts, linking to each of those published studies since 1960 in the area of consumer judgment and decision making that investigates memory. Finally we discuss implications of these studies for marketing management and suggest topics for futures studies in this area.The first empirical paper presents the Brazilian Portuguese versions of materials designed to evaluate individual differences that can affect judgment and decision making: the Numeracy Scale, the Subjective Numeracy Scale and the Cognitive Reflection Test. The Brazilian versions of tests were transculturally adapted and psychometric evaluated in a Brazilian sample. The original tests in English were translated to Brazilian Portuguese, following international rules of translation, reverse translation, comparison of versions for transcultural adaptation and face and content validation. The Brazilian Portuguese versions of the Numeracy Scale, the Subjective Numeracy Scale and the Cognitive Reflection Test were fast to be completed and well accepted by Brazilian participants; showed good psychometric performance, with adequate intern consistency indicators and convergent validity. These results show that the Brazilian Portuguese versions of the scales seems to be adequate tests to evaluate Brazilian participants numeracy and cognitive reflection.The second empirical paper of this dissertation investigates the relation between conjunctions and disjunction fallacies in probability judgments and conjunctions and disjunction fallacies in memory judgments. In this paper we report findings from an experiential learning paradigm, testing predictions of a mathematical model of conjunction and disjunction fallacies based on fuzzy-trace theory by manipulating the strength of verbatim and gist memories of prior choices and eliciting probability judgments about the past and future (Brainerd, Reyna & Aydin, 2010). As predicted by the theory, our results indicated that past and future judgments were related, as they are in memory. Moreover, disjunction and conjunction fallacies were proportional to the strength of gist memory but inversely proportional to the strength of verbatim memory. We observed the same expected effects of manipulations on memory and on probability judgments. Therefore, our study indicates a process overlap between memory and probability judgments.